The Role of Ultrasound and Computed Tomography in the Evaluation of Subcutaneous Esophageal Bypass in a Dysphagic Patient - Simone Vetere; Maria Luisa Mennini; Daniele Pironi; Manuela Brighi; Stefano Pontone (Case Reports in Pathology)
Several conditions require subcutaneous colon bypass surgery in the esophageal diseases treatment. Esophageal reconstructions are high risk procedures because of their morbidity and mortality rate. Cervical anastomotic strictures, colon transplant redundancy, recurrent dysphagia, intestinal obstruction, regurgitation, and aspiration are the most frequent late complications. The patient assessment should be performed with noninvasive methods in order to prevent long-term complications. We report the use of ultrasound (US) and computed tomography (CT) for evaluating a dysphagic patient, after subcutaneous esophageal bypass. A thorax and upper abdomen contrast media CT study with volume rendering reconstruction was performed in order to evaluate late post operative complications. In addition a US examination, performed after CT scan, was used for the assessment of the colonic wall and its vascularization. The subcutaneous esophageal bypass allowed for an effective ultrasound evaluation with no additional discomfort for the patient. ultrasonography has been shown effective in the esophageal bypass follow up, when subcutaneous colon bypass surgery was performed. The ultrasonography evaluation, also thanks to a Doppler flowmetry, allowed completing the patient assessment without additional invasive procedures or contrast. Thus it may be performed as a first level evaluation or in the follow up of subcutaneous esophageal bypass patients.